Analyzing the Spatial Dynamics of Deforestation in Brazilian Amazon. Issue 1 (23rd May 2016) - de Alencastro Bouchardet, Daniel; Alves Porsse, Alexandre; Timofeiczyk Junior, Romano
Abstract : Historically, development in Brazilian Amazon was promoted by permits of deforestation under soft territory control or supervision. However, due to the importance of this biome for biodiversity and ecosystem balance in a global perspective, Brazilian's government has tightened deforestation control. This work investigates the spatial pattern of deforestation in a cross‐section and time perspective using global and local spatial data analysis. Global results indicate the existence of high spatial correlation and that deforestation holds concentrated across space, despite the efficacy of policy mechanisms adopted for controlling and reducing the level of deforestation in Legal Amazon. Furthermore, local results support the hypothesis of high spillover effects. Considering the spatial analysis results, we highlight some implications for policy design aiming deforestation control.